Pengaruh Pembelajaran Kooperatif TerhadapKemampuan Sosial Anak Kelompok ADi Tk It Fatahillah Sukoharjo Tahun Ajaran 2016/2017 - Utami, Tri, Drs. Ilham Sunaryo, M.Pd. AUD (2017)
ABSTRACK TRI UTAMI/A520130011. The Influence of cooperative teaching learning toward young learner social skills at Group A class of TK IT Fatahillah Sukoharjo in Academic Year 2016/2017. Research Paper. Faculty of Teacher and Training Education, Universitas Muhammadiyah Surakarta, March, 2017. This study was arrange to know the significant influence of cooperative teaching learning toward young learner's social skills at Group A class of TK IT Fatahillah Sukoharjo. The method of this study was quantitative method by using this pre-experimental research as the design of the research. Pre-experimental design used one group pretest posttest design. The subject of the research was young learners of group A1 at TK IT Fatahillah Sukoharjo Academic Year 2016/2017. It consisted of 27 children. The technique of collecting the data of this research was by using observation, interview, test and documents. The technique of analyzing the data of this study used SPSS 16.0 for windows. The result of the analyzing the data by using ttest was that -15.758 < -ttable -1.7056 so H0 is rejected and Ha is accepted which mean that was the influence of cooperative teaching learning toward social prosperity. Key word: social prosperity, cooperative teaching learning.